2018
DOI: 10.1111/cmi.12827
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of helices α4 and α5 is required for insecticidal activity of Cry2Ab by promoting assembly of a prepore oligomeric structure

Abstract: Cry2Ab, a pore-forming toxin derived from Bacillus thuringiensis, is widely used as a bio-insecticide to control lepidopteran pests around the world. A previous study revealed that proteolytic activation of Cry2Ab by Plutella xylostella midgut juice was essential for its insecticidal activity against P. xylostella, although the exact molecular mechanism remained unknown. Here, we demonstrated for the first time that proteolysis of Cry2Ab uncovered an active region (the helices α4 and α5 in Domain I), which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 49 publications
2
19
1
Order By: Relevance
“…Most probably, these bands are residual incomplete trypsinized Cry1Ia forms, dragged through the toxin purification process. In conclusion, although some studies have reported the spontaneous formation of Cry protein oligomers in solution without being in contact with the membrane-like environment (i.e., Cry4Ba [55] or Cry2Ab [24]), in our study neither Cry1Ab nor Cry1Ia formed oligomers without being exposed to insect BBMV or cultured insect cells.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Most probably, these bands are residual incomplete trypsinized Cry1Ia forms, dragged through the toxin purification process. In conclusion, although some studies have reported the spontaneous formation of Cry protein oligomers in solution without being in contact with the membrane-like environment (i.e., Cry4Ba [55] or Cry2Ab [24]), in our study neither Cry1Ab nor Cry1Ia formed oligomers without being exposed to insect BBMV or cultured insect cells.…”
Section: Discussioncontrasting
confidence: 88%
“…In support of this model, several studies have reported that oligomerization plays a crucial role in the insecticidal activity of B. thuringiensis Cry toxins [18,38,45,46]. Moreover, Cry protein mutants that did not form oligomers, showed severely decreased toxicity [17,24,45]. Likewise, it has been shown that some Cry1A mutants that had lost their toxicity, were unable to oligomerize and to form pores [38,47].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Bacillus thuringiensis (Bt) is a gram-positive Bacterium that has been widely used in the control of agricultural and forestry pests such as Lepidoptera, Diptera, and Coleoptera due to its high specificity to target pests and non-target biosecurity (Schnepf et al, 1998). It is the most successful biological insecticide for major agricultural pests at present (Xu et al, 2018). Insecticidal protein are mainly Insecticidal crystal proteins (Cry) (Donovan et al, 2001(Donovan et al, , 2006Milne et al, 2008), Vegetative insecticidal proteins (Vips) (Estruch et al, 1996), and Secreted insecticidal proteins (Sip) (Donovan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The specific association between the hydrolyzed toxin and the brush border membrane vesicle (BBMV) is stronger than that between the original toxin and BBMV (Deist et al, 2014). CRY toxin breaks down the midgut cells of larvae after forming small pores (Pacheco et al, 2018;Xu et al, 2018). In the study of the insecticidal mechanism of Vip protein, it was found that Vip3Aa protein was activated by midgut proteases, which passed through the peritrophic membrane and were bound to the specific proteins in the midgut cells of the apical membrane, leading to the formation of pores and ultimately the death of insects (Ming et al, 2017).…”
Section: Introductionmentioning
confidence: 99%